Translation Shifts in Goenawan Mohamads Poem Collection On God and Other Unfinished Things (with Special Reference to Poem 33) - Christien Tiyuni Tirtayasa; Harris Hermansyah Setiajid (Journal of Language and Literature, 2018)
It has been acknowledged among translators that translating literary texts poses some difficulties. The translators have to make a decision among other choices related to diction. Not only diction, the inherent literary elements must also be rendered adequately in order to achieve literariness. Although the debate whether maintaining literary elements in a way that does not deviate from the source text or creating the elements anew is far from over, it is also worth noting that the essence of translation activity is not creating an original text, but it is a re-creation of meaning, a result of translators interpretation. Researches on literary translation are mostly about to what extent the translation is able to deliver a similar literary value, the strategies applied by the translators, and how the target text readers respond to the new creation of such texts. The elaboration of how the literary translation undergoes changes or shifts is not quite an issue in the field of literary translation research because it is considered too linguistic. However, in light of the Prague School tradition which examines shifts not only on surface level, but also on discourse level, the discussion on the shifts occurring in literary translation is worth conducting.This paper tries to take a look at the translation shifts occurring in the English version of Goenawan Mohamads poem collection entitled On God and Other Unfinished Things which is translated from Bahasa Indonesia Tuhan dan Hal-hal Yang Tak Selesai, especially poems 33 by comparing the literary elements in Bahasa Indonesia and English versions. The analysis departs from category shift in micro-level analysis to the semantic, textual, pragmatic, rhetorical, and stylistic components. The result shows that there are some significant distinctions concerning the linguistic and non-linguistic discrepancies found in Gunawan Mohamads poems and their English translation.Keywords: literary text, translation shift